Recent technical advancements and clinical applications of MR-guided radiotherapy in lung cancer treatment - Ma, Chi; Wang, Xiao; Nie, Ke; Xiong, Zhenyu; Xu, Keying; Yue, Ning; Zhang, Yin (Frontiers in Oncology, 2025)
Magnetic resonance-guided radiotherapy (MRgRT) represents a significant advancement in lung cancer treatment, integrating non-ionizing high-resolution magnetic resonance imaging (MRI) with linear accelerators to enable real-time tumor visualization and adaptive treatment planning. This review highlights recent advancements in MRgRT technology and explores its clinical applications, particularly in managing lung cancer patients. MRgRT has proven particularly advantageous in stereotactic body radiotherapy (SBRT) treatment for lung cancer, where motion management is critical due to respiratory-induced tumor motion. Real-time tumor monitoring and online adaptive plan modifications ensure target accuracy, reduce margins, and mitigate radiation-induced toxicity. Additionally, MRgRT could potentially allow multileaf collimator (MLC) tracking to further improve the treatment efficiency. Recent technological innovations, including AI-powered auto-contouring algorithms, deep-learning (DL) based prediction models, and adaptive treatment strategies, further optimize MRgRT by improving workflow efficiency and reducing treatment time. Despite these benefits, the widespread adoption of MRgRT is challenged by high infrastructure costs, prolonged treatment time, and the need for specialized expertise. Ongoing research is addressing these challenges through workflow optimization, remote treatment models, and AI-driven decision support systems. As MRgRT technology continues to evolve, its integration with functional imaging, radiomics, and adaptive protocols is expected to expand its applications beyond lung cancer treatment. MRgRT represents a paradigm shift in precision oncology, delivering personalized care. Future research and prospective clinical trials should be warranted to generate high-quality clinical evidence supporting MRgRT’s clinical adoption for lung cancer patient management. As these advancements progress, MRgRT is poised to transform the future of lung cancer treatment.